2012
DOI: 10.1007/s12094-012-0772-8
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver variability in target volume delineation in postoperative radiochemotherapy for gastric cancer. A pilot prospective study

Abstract: A significant IV in target delineation that can be attributed to many factors depends more on patients' characteristics than RO delineating decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…A common theme of many publications is the identified need for multidisciplinary input into target volume delineation. This includes involvement of surgeons, pathologists, radiologists and other interventional specialists who have been involved in the diagnostic workup . Radiologists in particular are helpful in image interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A common theme of many publications is the identified need for multidisciplinary input into target volume delineation. This includes involvement of surgeons, pathologists, radiologists and other interventional specialists who have been involved in the diagnostic workup . Radiologists in particular are helpful in image interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…This includes involvement of surgeons, pathologists, radiologists and other interventional specialists who have been involved in the diagnostic workup. 72,87,88 Radiologists in particular are helpful in image interpretation. Dimigen et al 89 evaluated the effect of a radiologist working within an oncology department and found that radiology review of 56 CT scans led to a change in target volume in 20% of cases and OAR in 5%.…”
Section: Discussionmentioning
confidence: 99%
“…A large inter- and intraobserver variability in target volume delineation was reported in GC patients 52, 53. In a questionnaire, 75 % of respondents indicated the elective nodal area as the major subjective difficulty 54.…”
Section: Lymph Node Considerationsmentioning
confidence: 99%
“…Accurate target and organ-at-risk (OAR) delineation from CT and/or MR simulation images is an essential step in assuring accurate radiation therapy planning. [1][2][3][4] Due to the limitations of current imaging techniques in visualizing human anatomy (e.g., insufficient contrast, resolution, or both) as well as inherent anatomical variability among individuals, both manual and automated structure contouring processes are subject to errors. These errors include mislabeling, missed slices, overlapped structures, isolated voxels or small regions, extremely large or small slices, and structure volume and location distortions.…”
Section: Introductionmentioning
confidence: 99%